Structural, thermal and optical properties of magnesium ion conducting biopolymer electrolytes for supercapacitor applications. (2022) - Sadiq, Mohd; Chaurasia, S.K.; Kr Singh, Anjani; Pandey, Raghvendra; Shankar Yadav, Hari; Hasan Raza, M.M.; Kumar, Yogesh; Singh, P.K.; Zulfequar, M.; Ali, Javid
Abstract: This paper reports the physical properties of magnesium ion (Mg 2+ ) conducting biopolymer electrolyte films of cellulose acetate (CA) + xwt.% Mg(ClO4 )2 containing different amounts of magnesium salt (x = 10, 20, 30, 40 and 50 wt%) which have been prepared by the solution cast technique. The prepared biopolymer films were characterised by XRD, FTIR, DSC and UV–vis spectroscopy. The structural analysis carried out by X-ray diffraction (XRD) study confirms the structural changes & decrease in the degree of crystallinity of the host biopolymer matrix CA upon incorporation of magnesium salts Mg(ClO4 )2 . And this effect is more pronounced at higher loading. The DSC thermograms of the electrolyte films showed that the glass transition temperature (Tg ) increases with the increase of salt content in the biopolymer CA matrix which is attributed to the restriction in the mobility of the polymeric chains. This hindrance was caused by the high density constituent ions of dopant salt. Fourier transform infrared (FTIR) spectroscopic study confirms the complexation between the cations of the dopant salt (Mg 2+ ) and ester group (i.e. C = O) of the biopolymer chain owing to Lewis acid-base interactions. The UV–visible spectroscopic analysis demonstreted that optical absorption edge as well as direct & indirect optical band gap decreases with the incease of the concentration of dopant magnesium salt.